Comparison of two static methods of saddle height adjustment for cyclists of different morphologies - Millour, G.; Duc, S.; Puel, F.; Bertucci, W. (Sports Biomechanics, 2021)
Methods based on inseam length (IL) for saddle height adjustment in cycling are frequently employed. However, these methods were designed for medium-sized people. The aim of this study was to evaluate knee angle during pedalling by 2D video analysis and perceived comfort using a subjective scale under three saddle height conditions: (1) self-selected saddle height, (2) Genzling method (0.885 × IL) and (3) Hamley method (1.09 × IL minus crank arm length). Twenty-six cyclists of heterogeneous morphology were recruited. Three groups were determined based on IL: Short (IL < 0.8 m), Medium (0.8 m < IL< 0.88 m) and Long (IL > 0.88 m). The results showed that Medium and Long IL groups usually rode with saddle heights allowing knee angles consistent with those previously shown to prevent injuries (30°-40°). However, Short IL group, who were all children, self-selected a too low saddle height (knee angle was too large). Genzling and Hamley methods gave identical results for Medium IL group, permitting knee angles in the range of 30°-40°. However, both methods caused important differences between Short and Long IL groups. Hamley method was more suitable for short ILs, while Genzling method was more suitable for long ILs.